Hungarian Diplomacy towards Africa: Forging Bilateral Relations in the 1960s and 1970s - István Tarrósy; Dániel Solymári (Modern Africa, 2025)
One of the defining facts of Hungary’s foreign policy is that it had political sovereignty only for short periods until 1989. At the beginning of the 1960s a pragmatic and constructive Hungarian foreign policy began to take shape, which, in the period of the détente within the Soviet Bloc, could follow a relatively independent path. Sub-Saharan Africa (SSA) was one of its key relations, and it became one of the priority foreign policy directions of Hungarian diplomacy. The diplomatic steps taken towards SSA, and the formation of the Hungarian Africa policy during the détente period, we argue, offer relevant considerations from a pragmatic international relations perspective even today. Based on archival and printed press sources, the article provides an analysis of Hungary’s “African turn” between 1960 and 1970.